Battle Angel Alita : deluxe edition. Volume 2 - Kishiro, Yukito (Kodansha Comics, 2018)
"In a dump in the lawless settlement of Scrapyard, far beneath the mysterious space city of Zalem, disgraced cyber-doctor Daisuke Ido makes a strange find: the detached head of a cyborg woman who has lost all her memories. He names her Alita and equips her with a powerful new body, the Berserker. While Alita remembers no details of her former life, a moment of desperation reawakens in her nerves the legendary school of martial arts known as Panzer Kunst. In a place where there is no justice but what people make for themselves, Alita decides to become a hunter-killer, tracking down and taking out those who prey on the weak. But can she hold onto her humanity as she begins to revel in her own bloodlust?"--Publisher's website.